The Agility Mindset : How reframing flexible working delivers competitive advantage - Cannon, Fiona (Palgrave Macmillan, 2017)
Shows how to unlock the massive efficiency savings and productivity gains by reframing the approach to flexible working by concentrating on workforce agility. We know that organizations don't need the same number of workers 9-5, five days a week 52 weeks a year. We know that not all of the best talent will work when and where we want. We know that command and control Taylorism stifles innovation and creativity. So why do we keep thinking of flexible working as a cost to the organization? A simple mindset shift is all that is required to grasp the opportunity that smart organizations are already exploiting. Stop thinking about "flexible working" and start thinking about "workforce agility". By creating win-win working practices you can attract the best talent by offering the flexibility they crave and secure the agile, just-in-time workforce that can get the job done. The Agile Future Forum, a business-to-business initiative started by 22 founder members -- mostly CEOS of big employers including BT, Lloyds Banking Group, Cisco, Tesco, KPMG, HM Treasury and Ford -- have conducted case studies and a collated best practice from world class organisations which show that a more agile approach to flexible working not only delivers better performance but can also save between 3 and 13% of personnel costs. The Agility Mindset blends the insights of scores of CEOs, along with the frontline experience of practising managers to create this very practical guide. Based on rigorous research, but packed with practical diagnostics and frameworks, the book shows you how to create a fit for purpose workplace in a world where only the agile will flourish.
Keywords: Flexible work arrangements.; Organizational change.; Organizational effectiveness.; Employee motivation.; elektronické knihy; electronic books